2009
DOI: 10.1371/journal.pmed.1000070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rapid Malaria Diagnostic Tests on Treatment and Health Outcome in Fever Patients, Zanzibar—A Crossover Validation Study

Abstract: Anders Bjorkman and colleagues report results from a cross-over trial evaluating rapid diagnostic testing for malaria diagnosis in Zanzibar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
158
11
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(186 citation statements)
references
References 24 publications
15
158
11
2
Order By: Relevance
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…When good-quality malaria laboratory diagnosis is available and assuming test results are followed, prescribing of antimalarials to patients with nonmalaria fever can be minimized. 12,[31][32][33] Although resources are currently unavailable to fully equip health centers with a wide array of laboratory tests, periodic systematic evaluation of prevalent non-malarial febrile diseases could be conducted to determine the most critical laboratory tests and suggest what anti-infective agents should be recommended for treatment. Such streamlining would represent a more efficient use of limited resources and could be a portal for integrated clinical and laboratory services for multiple diseases.…”
Section: Integrated Fever Managementmentioning
confidence: 99%
“…Some studies show that use of RDTs increases antibiotic prescribing in malaria-negative patients [20,21] (Table 2). If the disease is a common cold, antibiotics should generally be avoided.…”
Section: Review Of the Evidence For The Assumptions Underlying Who's mentioning
confidence: 99%